2021
DOI: 10.1055/s-0041-1736217
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Tuberosity Transposition Fixation with a Locking Plate during Medial Patellar Luxation Surgery: An Ex Vivo Mechanical Study

Abstract: Objectives The purpose of this study was to compare the load at failure, stiffness and mode of failure between three types of tibial tuberosity transposition fixation techniques: (a) pin and figure-8 tension band wire (Pin-TBW), (b) locking plate with pin and a tension band wire (Plate-Pin-TBW) and (c) locking plate with a pin (Plate-Pin). Methods Six pairs of raccoon dog cadaveric tibiae were tested in Phase I Pin-TBW versus Plate-Pin-TBW and seven pairs in Phase II Plate-Pin-TBW versus Plate-Pin. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…The load to failure reported in our study was approximately two times higher than that reported in a similar study performed with tibiae from raccoon dogs, which have similar mean body weights to the specimens used in the present study ( 12 ). The raccoon dog study reported mean weights of 7.1 kg and 6.2 kg.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…The load to failure reported in our study was approximately two times higher than that reported in a similar study performed with tibiae from raccoon dogs, which have similar mean body weights to the specimens used in the present study ( 12 ). The raccoon dog study reported mean weights of 7.1 kg and 6.2 kg.…”
Section: Discussionsupporting
confidence: 48%
“…Another limitation is the broad range of body weight of the dogs used for the study. We selected small breed dogs because of the clinical significance, which may be considered more relevant in comparison to other similar studies that utilized larger cadavers ( 12 , 18 , 28–30 ). The wide range of tibia size would likely have caused variability in mean stiffness and maximum load at failure, as well as failure modes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 A biomechanical study has shown a higher load to tibial tuberosity avulsion or fracture with a Kirschner wire plus locking plate compared to Kirschner wire plus tension band wire. 27 Clinical results of TTA plates or locking plates for TTT have not been published.…”
Section: Discussionmentioning
confidence: 99%
“…1 3 Multiple methods for fixation of the tibial tuberosity osteotomy have been described in the veterinary literature including lag screw fixation, 4 use of a single Kirschner wire, 5 6 7 double Kirschner wires, 1 2 3 8 9 or locking plate fixation. 10 Prior investigators have proposed that Kirschner wires should be oriented caudoproximally as this has been associated with increased tensile strength, 3 6 9 however, caudodistal angulation is described and routinely performed clinically. 11 One study by Cashmore and colleagues found that the more caudodistally the Kirschner wires were directed, the greater the risk for tibial tuberosity avulsion.…”
Section: Introductionmentioning
confidence: 99%